FUNCTIONALITY OF CHARACTERS OF SATIRIC TEXT (ON MATERIAL OF WORKS OF IVAN FRANKO, LES’ MARTOVYCH AND STEPHEN KOVALIV) - Marchuk, G. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article is devoted research of features of the use of symbolism of satiric appearance as mean of design of satiric text in works of the Galychyna writers on the fracture of XIX-XX centuries. As a result of the conducted analysis of text material similarity appears artistically - stylistic receptions of satiric design of reality .